2013
DOI: 10.1111/1574-6941.12235
|View full text |Cite
|
Sign up to set email alerts
|

Inferring community dynamics of organohalide-respiring bacteria in chemostats by covariance ofrdhAgene abundance

Abstract: We have developed a novel approach to identifying and quantifying closely related organohalide-respiring bacteria. Our approach made use of the unique genomic associations of specific reductive dehalogenase subunit A encoding genes (rdhA) that exist in known strains of Dehalococcoides mccartyi and Desulfitobacterium and the distinguishing covariance pattern of observed rdhA genes to assign genes to unknown strains. To test this approach, we operated five anaerobic reductively dechlorinating chemostats for 3-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…To investigate the ecological effects of 1,2-DCA exposure on Dehalococcoides populations within a chloroethene-dehalogenating consortium, we used a TCE-fed reactor (EV-5), maintained for the 8 years prior, to seed a set of experimental reactors: EV-3, EV-TCE, EV-P (Table ). A previous study indicated that the parent reactor EV-5 was comprised of multiple populations of organohalide-respiring bacteria, and our recent metagenomic analysis revealed that it contained distinct tceA -containing and vcrA -containing populations. Reactor EV-3 was exposed to a changing mixture of TCE and 1,2-DCA over the course of a year and then fed 1,2-DCA only.…”
Section: Results and Discussionmentioning
confidence: 65%
“…To investigate the ecological effects of 1,2-DCA exposure on Dehalococcoides populations within a chloroethene-dehalogenating consortium, we used a TCE-fed reactor (EV-5), maintained for the 8 years prior, to seed a set of experimental reactors: EV-3, EV-TCE, EV-P (Table ). A previous study indicated that the parent reactor EV-5 was comprised of multiple populations of organohalide-respiring bacteria, and our recent metagenomic analysis revealed that it contained distinct tceA -containing and vcrA -containing populations. Reactor EV-3 was exposed to a changing mixture of TCE and 1,2-DCA over the course of a year and then fed 1,2-DCA only.…”
Section: Results and Discussionmentioning
confidence: 65%
“…Therefore, strain specific nodes are more likely to connect with other nodes from the same cluster; the consensus network therefore represented at least two populations of Dhc . Overall, the slight genomic variations between strains of Dhc [41] lead to different survival patterns, metabolic capabilities, and environmental responses as experimentally displayed in the suitability of various strains to differing culturing conditions in Marshall et al [42]. …”
Section: Resultsmentioning
confidence: 99%
“…The study was conducted in a continuous flow column packed with quartz Ottawa sand. The column was bioaugmented with Evanite culture (EV) that contains strains of Dehalococcoides mccartyi (Dhc) (Behrens et al, 2008;Marshall et al, 2013) that is capable of transforming PCE to ethene (ETH) (Yu et al, 2005). The reductive dehalogenase (rdh) genes in the Evenite culture were identified as being closely related to the population of Dhc previously found under chemostat growth conditions (Marshall et al, 2013;Mayer-Blackwell et al, 2014),…”
Section: -mentioning
confidence: 99%
“…The column was bioaugmented with the EV mixed dehalogenating culture that contained at least two strains of Dehalococcoides mccartyi (Marshall et al, 2013). Molecular characterization of the EV culture in a previous column study where the EV was bioagumented showed 73% of bacteria in the EV culture were strains of Dhc (Azizian et al, 2008).…”
Section: Bioaugmentation Culturementioning
confidence: 99%